POLITICAL INSTABILITY AND INSTITUTIONAL INTERPLAY: A STUDY OF PAKISTAN’S FRAGILE DEMOCRATIC JOURNEY 1947-1969 (Contemporary Journal of Social Science Review, 2025)
This research article explores the democratic and political developments in Pakistan during its initial years from 1947 to 1969. The article primarily focuses on the interplay between the bureaucracy, military, and political elites. The study examines how institutional dynamics and leadership decisions shaped Pakistan's democratic and political trajectory, leading to periodic disruptions in democratic processes. It highlights the central role of the bureaucracy, the military's increasing involvement in politics, and the political elite's contribution to institutional instability. The article provides a critical analysis of democratic challenges and provides insights into the long-term implications of these developments on the country's political culture.